ANALISIS POLA KEPUASAN PENGUNJUNG TERHADAP DAYA TARIK WISATA TAMAN SARI YOGYAKARTA DENGAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Irawati, Novi; Wahyuni, Sri (Jurnal Bulletin, 2019)
Visitor Satisfaction is a comparison between the performance expected by the customer compared to the actual performance in the field. When actual performance is higher than customer expectations, the customer feels satisfied and vice versa. The purpose of this study is to determine the performance of managers in providing good service to tourists and measuring customer satisfaction to the services provided while in Taman Sari Yogyakarta Tourism Object, by knowing the quality of performance of officers or managers in providing services to tourists are expected to be able to make improvements and evaluation of the management of servants so that the object of Taman Sari Cultural Tourism can be a tourist attraction that is in demand by tourists not only because of its tourist attraction but because of the quality of the servants who are good to tourists.